Survey on serum protein electrophoresis and recommendations for standardised reporting - Sthaneshwar, Pavai; C Thambiah, Subashini; Mat Salleh, Mohd Jamsani; Nasuruddin, Dian Nasriana; Ahmad Zabidi, Nurul Faatima; Mohammed Jelani, Aniza; Mohd Ismail, Aletza; Lai, Leslie Charles; Gan, Gin Gin (Malaysian Society of Pathologists, 2021)
Introduction: Serum protein electrophoresis (SPE) is a well-established laboratory technique. However, reporting of results varies considerably between laboratories. The variation in reporting can cause confusion to the clinician with a potential of adversely impacting patient care. The purpose of the survey was to find out the variation in reporting and to prepare recommendations to the Malaysian laboratories based on the survey to reduce both the variation in reporting between laboratories and the risk of misinterpretation of reports. Materials and Methods: To determine the extent of variation in reporting of protein electrophoresis results questionnaires were distributed to the pathologists of various laboratories in Malaysia regarding the method, quantification of paraprotein concentrations and immunoglobulin assays, and information regarding current laboratory electrophoresis practices. Results: Variation was found in the following reporting practices: (a) screening protocol; (b) reporting of serum albumin; (c) numerical reporting of protein fractions and paraprotein; (d) co-migration of a paraprotein with a normal serum protein; (e) reporting of multiple paraprotein bands (f) appearance of small abnormal band and oligoclonal bands and (g) communication about of interferences. Conclusion: The pathologists of the country made recommendations on the reporting of protein electrophoresis. Harmonised reporting will reduce inconsistency, variation in reporting, improve the quality of the report and most importantly improve patient care.